Smartphones in Family Wellbeing: A Study on Access and Use of Food and Health Apps among Women Smartphone Users (International Journal of Food and Nutritional Sciences, 2022)
Smartphones play a prominent role in providing access to health and nutrition-related content from various sources. People are more likely to adopt healthier eating habits and make better food decisions when exposed to such content, ensuring their families wellbeing. Introduction to healthy food products and information about their benefits, ease, and mode of use can enable more people to adopt healthier eating habits and make better food decisions for their families. Availability of food recipes, health care routines, nutrition-related information, and weight management programs in digital platforms enable increased use. Both men and women use digital health and nutrition apps to ensure their own as well as the wellbeing of their families. Mobile applications are predominantly used in self-monitoring of individuals’ food intake and related physical activities, promoting a healthy lifestyle. However, the usage in rural regions, especially among women, must be explored. This paper explores the access and use of food and health apps among women smartphone users in rural households. Regarding women smartphone users in rural regions, this study identifies that their usage is high towards referring to cooking recipes and health information.